A cross sectional study on the prescribing pattern, self medication and adverse reactions associated with topical corticosteroids - Teja, Venepalli N.; Sree, Podila K.; Yadala, Venkata R.; M., Arun Kumar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Glucocorticosteroids, one of the common drugs used by the dermatologists brought a revolutionary change in their practice. Unfortunately steroids are misused in dermatological panacea due to dramatic relief in inflammatory and pruritic skin conditions but may lead to deleterious effects if irrationally used. Hence this study was planned to know the prescribing pattern of corticosteroids. Methods: It was a cross sectional observational study. The prescriptions of patient attending the dermatology OPD were screened for the usage of the corticosteroids. The demographic data, chief complaints, diagnosis and the details of the drugs was collected. Results: Out of 384 prescriptions screened, 14.06% were prescribed corticosteroids. Average number of drugs per prescription was 2.28±0.83. Polypharmacy (≥4 drugs) observed in 9.26% of prescriptions. Corticosteroids prescribed by generic name were 24.07% and brand name was 75.93%. Corticosteroids alone prescribed in 38.89% and along with antihistaminics/antibiotics/emollients in 61.11%. Topical corticosteroids prescribed in 79.6% and 20.4% by systemic route. Moderately potent steroids prescribed in 74.42% followed by potent (13.95%) and very potent steroids (11.63%). Patients on corticosteroid self-medication were 28%, among them 4 developed adverse reactions with severe acneiform eruptions over the face. No fixed dose combination drugs were prescribed. Conclusions: In this study we observed the rationale and safe prescribing pattern. However, the corticosteroids prescribed by brand names (75.93%) were more than generic names (24.07%), information about the strength of the steroid not mentioned and usage of emollients was less. This indicates the need for continuous medical education for the clinicians.